Reporting of climate change news in three Nigerian newspapers (2012)
The trend of news frame in the print media has implications for public perception of emerging development issues and actions that members of the public in general and farmers in particular will take in similar situations in the future. Combining the occurrence of climate change topical news variables and framing theories, this study content-analysed 111 climate news items framed in three Nigerian newspapers (the Guardian, Punch and Nigerian Tribune) between January 2010 and June 2011. Variables measured included news types, placement, sources, space allotted and period of report of climate change related stories. Data were analysed using both descriptive (frequency, percentage) and inferential (chi-square) statistics at p<0.05. Across the three newspapers, types of news reported as a result of climate change were flooding (41.4%) and oil spillage (27.9%). They were strategically placed at the front (32.4%) middle (36.0%) and back (31.5%) pages of the newspapers. The newspapers quoted news reporters of other media organizations (62.2%) and government officials (22.5%) as major sources of their climates change information. Space allocated to climate change news was higher in the Guardian newspaper (897cm2) compared to the Punch and. The Nigerian Tribune (884cm2). Major frames found in these dailies include warning, solution, disaster, awareness, call for assistance and blames. Types of climate change news did not affect placement given to coverage of such news (X2 =13.45; p=0.20). In spite of competition for space and prominence by wide range of development issues, climate change news coverage relatively enjoyed prominence. Therefore, efforts should be made to sustain this given the menace climate change portends in the face of any neglect by stakeholders especially the media.